The effects of CFRP orientation on the strengthening of reinforced concrete structures. (1st April 2016) - Lima, Mehdi M.; Doh, Jeung‐Hwan; Hadi, Muhammad N. S.; Miller, Dane
Summary: In recent years, the strengthening and retrofitting of structural members using externally bonded carbon fibre reinforced polymer (CFRP) materials has gained a great deal of attention. This has eventuated from the superior properties of composite materials, including high elastic modulus, higher strengths and lighter weights. This paper presents a finite element analysis that has been validated against laboratory tests of two reinforced concrete (RC) beams, two columns, two slabs and six walls. The main focus is on the ultimate failure load of these members as they have different CFRP orientations to the loading direction. The analysis result shows a sound agreement with the experimental data regarding the ultimate failure load of RC samples, except for the RC wall. In fact, the RC wall, while under eccentric axial load, confirmed that the CFRP orientation was parallel to the loading direction, and it proved to be an insignificant contribution in the ultimate failure load of the samples. This finding demonstrates that more experiments should be considered when investigating the influence of CFRP on the ultimate strength of strengthened RC walls. Copyright © 2016 John Wiley & Sons, Ltd.